Positive Legislature Decisions by the Constitutional Court: Putusan Positive Legislature oleh Mahkamah Konstitusi - Efendi, Muhammad Alief Farezi; Muhtadi, Muhtadi; Saleh, Ahmad (Jurnal Konstitusi, 2023)
The shift in the role of the Constitutional Court, which has tended tobecome a positive legislator in the last 11 years, began with the existenceof Constitutional Court Decision Number 48/PUU-IX/2011, which, in itsessence, eliminated the limitations on the role of constitutional judges inrendering decisions with a regulatory nature. Consequently, in the last11 years, out of 198 accepted decisions, 107 positive legislative decisionswere identified, and when presented, these positive legislative decisionsconstituted a majority of 54% of the total decisions. The practice ofpositive legislation itself appears to be ineffective, primarily due tothe fact that out of the total 107 decisions, only 26 decisions wereimplemented by the addressees of the decisions. Through normativejuridical research using a statute approach and conceptual approach,this study is focused on understanding why the practice of positivelegislation is not optimal. This is because there is no legal basis, it doesnot fall within the Constitutional Court’s domain to decide cases witha regulatory nature, and there is no obligation for the addressees ofthe decisions to implement positive legislative decisions.